China’s Investment in the East Coast Railway Line (ECRL) Project in Malaysia as a Strategisation of Space - Dini Putri Saraswati; Arnaldi Nasrum (TRANSBORDERS: International Relations Journal, 2026)
China has cooperated with Malaysia to construct the East Coast Railway Line (ECRL) project as an alternative to fulfil China’s interest for energy supply to sustain its industrial development. ECRL project can tackle the challenges of Straits of Malacca that obstruct China to transport oil from middle East. ECRL project can links port of Klang to Port of Kuantan by railway and then continued to mainland China by vessels. This article explores how China employs its investment in the ECRL Project in Malaysia as a strategisation of space. The theory of smart and hard power as a theoretical framework in this article helps observe the efforts China taken to influence Malaysia to construct ECRL project. This article is divided five parts. Firstly, it talks about the ECRL project in Malaysia and the role of China. Secondly, it breaks down the employed theoretical framework namely the smart power theory related to connectivity. Thirdly is about the smart power strategy that China uses to show its dominance in the region. Fourthly, it will highlight the relation of the ECRL project to Chinese strategisation of interest discussing about how the project is mutually strategic for both countries. Lastly, the part of analysis that demonstrates Chinese investment in the ECRL project in Malaysia is Chinese strategisation of space by exercising its smart power and forming connectivity among China, Malaysia, and other oil-exporting countries for China’s interest in oil.